Perbandingan Crunch Free ABS dengan Abdominal Exercise Kombinasi Bracing dalam Mengurangi Diastasis Recti pada Postnatal Pervaginam di RS Efarina Pematangsiantar - Muliati, Muliati; Napitu, Marolop Parlindungan; Purba, Yeni Trisna; Togatorop, Margaretha (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2024)
Diastasis recti is often characterized by a prominent midline following increased intra-abdominal pressure, thinning and widening of the linea alba, coupled with weakness of the abdominal wall muscles. Diastasis recti bise causes complications such as pelvic floor muscle dysfunction, umbilical hernia, incontinence, and prolapse of the uterus. To return the abdominal muscles to normal again, crunch free abs exercises or andominal exercises combined with bracing can be done. This study aims to determine the comparison of crunch free abs with abdominal exercises combined with bracing in reducing diastasis recti in postnatal vaginal delivery. This study used a quasi-experimental design with a pretest – posttest design. The sample was divided into two groups, group A was given the crunch free abs treatment and group B was given the combination bracing abdominal exercise treatment. Based on the results of statistical tests with Mann Whitney obtained a significance result of 0.747 (> 0.05) so that it can guarantee that there is no difference in the effect of crunch free abs with abdominal exercises on the reduction of rectal diastasis in postnatal vaginal women.